Gestión administrativa y suincidencia en los planes y programas del hospital Sagrado Corazón de Jesús área # 2 del cantón Quevedo, Año 2014, Manual de Gestión. - Zambrano Bazurto, Ana Dolores (2015)
The Sacred Heart of Jesus Hospital Area # 2, Quevedo Canton, is a medical unit dedicated to the provision of public health in general medicine, medical specialties, clinical laboratory, hospitalization, ICU, emergency and general services, which responds to a hospital second level. That health unit to provide different public health services must comply with administrative processes to comply with institutional plans and programs that attach to each period. That legislation is not fulfilled as required by law, therefore it is necessary to establish the factors that affect not achieve the necessary performance, which is required to comply with the Good Life in the target population of that jurisdiction. The factors that impede the achievement of plans and health programs are the small number of staff and health professionals, drug shortages, poor hospital infrastructure to the high demand for health services, reduced equipment and medical instruments and need to extend the hours of care. This reduces the operational capacity of the health unit management level reached 56%, which is rated as poor. Having determined the administrative reality of the medical unit is considered appropriate to increase the budget to incorporate more staff in the health area and services, acquire greater volume of medical supplies and medicines, expand the hospital infrastructure, and purchase new and modern equipment and medical instruments. Given all this, it is considered appropriate to develop a manual of administrative management for the effective implementation of plans and health programs assigned to the medical unit in favor of the local population of Quevedo and their areas of influence.